1994
DOI: 10.1021/bi00188a024
|View full text |Cite
|
Sign up to set email alerts
|

Broad Spectrum Aminoglycoside Phosphotransferase Type III from Enterococcus: Overexpression, Purification, and Substrate Specificity

Abstract: The aminoglycoside phosphotransferases (APHs) are responsible for the bacterial inactivation of many clinically useful aminoglycoside antibiotics. We report the characterization of an enterococcal enzyme, APH(3')-IIIa, which inactivates a broad spectrum of aminoglycosides by ATP-dependent O-phosphorylation. Overproduction of APH(3')-IIIa has permitted the isolation of 30-40 mg of pure protein/(L of cell culture). Purified APH(3')-IIIa is a mixture of monomer and dimer which is slowly converted to dimer only ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
174
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(195 citation statements)
references
References 39 publications
20
174
1
Order By: Relevance
“…Kinetic Assay-A continuous spectrophotometric assay that couples aminoglycoside phosphorylation with lactate production was used to measure the consumption of ATP or GTP as a function of NADH oxidation (19). Data were collected at 37°C with a SpectraMax 190 absorbance microplate reader, where each assay was performed with a total volume of 200 l, containing 50 mM Tris-HCl at pH 7.5, 40 mM potassium chloride, 10 mM magnesium chloride, 3.0 mM phosphoenolpyruvate, 3.0 mM tobramycin, 360 mM ␤-nicotinamide adenine dinucleotide (reduced), 20 units/ml pyruvate kinase, and 25 units/ml lactate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic Assay-A continuous spectrophotometric assay that couples aminoglycoside phosphorylation with lactate production was used to measure the consumption of ATP or GTP as a function of NADH oxidation (19). Data were collected at 37°C with a SpectraMax 190 absorbance microplate reader, where each assay was performed with a total volume of 200 l, containing 50 mM Tris-HCl at pH 7.5, 40 mM potassium chloride, 10 mM magnesium chloride, 3.0 mM phosphoenolpyruvate, 3.0 mM tobramycin, 360 mM ␤-nicotinamide adenine dinucleotide (reduced), 20 units/ml pyruvate kinase, and 25 units/ml lactate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
“…The assay is described in greater detail elsewhere (3). When the kinetic parameters of the D261A were determined for neomycin we found that the K m was near the detection limit for the assay described above.…”
Section: Kinetic Analysis Of Mutant Aph(3ј)-iiia Proteins-mentioning
confidence: 92%
“…The forward PCR primer has been described previously (3). The D261A, E262A, F264A, and D261A/⌬Phe 264 double mutant were similarly generated using the mutagenic oligonucleotides, 5Ј-CCCGAAGC-TTCTAAAACAATTCAGCCAGTAAAATATAATA-3Ј, 5Ј-CCCGAAGCT-TCTAAAACAATGCATCCAGTAAAAT-3Ј, 5Ј-CGAAGCTTGGATCCCT-AAGCCAATTCATCCA-3Ј and 5Ј-CCCGAAGCTTCTACAATTCAGCC-AGTAAAATATAATATTTTA-3Ј, respectively, as the reverse primers.…”
Section: Site-directed Mutagenesis Of Aph(3ј)-iiia-thementioning
confidence: 99%
See 2 more Smart Citations